Situation conditioned transformations of recent lyrics - Kleňhová, Eliška (Bohemica Olomucensia, 2013)
The article deals with the transformation of recent modern lyrics in the world of live concerts. Czech texts of some recent middle stream music groups and chosen folk singers were put under examination. First, the article shortly inquires into specific features of songs in general (especially their heterogenous temper and tension between the written lyrics and its sound realization), second, it focuses on the specificity of concerts environment and its effect on the transformation of lyrics. Transformations of the texts are demonstrated on particular examples.